COMPARISON OF INTAKE VALVE DEPOSIT TEST METHOD BETWEEN ASTM D6201 AND STATIONARY MOTORCYCLE TEST - Agustiawan, Andika
To determine quality of fuel that meet the Worldwide Fuel Charter category, a test with American Standard Testing and Material is required. However, testing with the ASTM D6201 standard is very costly and requires long preparation times. Therefore, an alternative method is needed to replace the ASTM D6201 test method. In spite of that, the result of this alternative method needs to be compared first to determine its feasibility in replacing the ASTM D6201 test method. Based on this, the researcher formulated the research title “Comparison of Intake Valve Depsosit Test Method Between ASTM D6201 and Stationary Motorcycle Test”. The alternative test method that being developed uses a Honda Vario 125 CC SOHC engine that running at 1750 RPM during the testing. While, ASTM D6201 uses a Ford Engine 2300 L engine that consists of 4 cylinders. Essentially, the fundamental difference that relies between these 2 methods is the engine that being used. The alternative test method was evaluated and conducted according to ASTM D6201 standard to enchance the accuracy of the results. These results will evaluate Intake Valve Deposits (IVD), Combustion Chamber Deposits (CCD), Injector Flow Loss (IFL), Ring Sticking (RS), and valve sticking (VS). Researchers conducted a correlation by examining the engine characteristics and testing operations parameters, such as cylinder volume, clearance volume, combustion chamber volume, intake valve surface area, intake valve area without stem, total fuel consumption, operational rotational speed, numbers of injector sprays, and combination of all. The requirements for the alternative test method to replace the ASTM D6201 test if the theoretical deposit obtained and the experimental deposit that obtained from Honda Vario have an error that less than 5%. Based on the calculations, all correlation methods have an error more than 5%. Therefore, it can be concluded that the alternative test method cannot replace the ASTM D6201 test method.